Association between the dietary omega-6 to omega-3 fatty acid ratio and age-related macular degeneration in Korean adults - Won Jang; Yuna Kim; Hyesook Kim (Nutrition Journal)
Abstract Background Long-chain polyunsaturated fatty acids of the omega-6 and omega-3 families affect processes implicated in vascular and neural retinal disease pathogenesis. This study aimed to investigate the association between the dietary omega-6 to omega-3 fatty acid ratio and age-related macular degeneration (AMD). Methods We conducted a cross-sectional analysis using a nationwide representative sample of older adults (≥ 50 years), including 1,944 men and 2,592 women, from the Korea National Health and Nutrition Examination Survey (2017–2018). Omega-6 and omega-3 fatty acid intakes were collected through a 24-hour recall method and used to calculate the omega-6 to omega-3 fatty acid ratio. Associations between the ratio and AMD were determined using odds ratios (ORs) from multivariate logistic regressions. Results The prevalence of AMD was 19.8% and 17.7% in Korean men and women, respectively. In women, the multivariable-adjusted OR for incurring AMD was significantly higher in the 2nd (OR = 1.36; 95% CI = 1.02–1.81) and 3rd (OR = 1.36; 95% CI = 1.02–1.83) tertiles of the dietary omega-6 to omega-3 fatty acid ratio than in the 1st tertile (OR = 1, the reference OR) (P = 0.036 for this trend). However, this association was not observed in men. Conclusions These results suggest that high omega-6 to omega-3 fatty acid ratios may be associated with an increased prevalence of AMD among Korean women.